Immunomodulatory Activity of Octenyl Succinic Anhydride Modified Porang (Amorphophallus oncophyllus) Glucomannan on Mouse Macrophage-Like J774.1 Cells and Mouse Primary Peritoneal Macrophages - Gurusmatika, Sellen (Molecules, 2017)
Porang is a local plant of Indonesia, which has a high content of glucomannan. In this study, porang glucomannan (PG) was esterified with octenyl succinic anhydride (OSA) to enhance emulsion properties to be widely used in food industry. OSA-modified PG (OSA-PG) enhanced the phagocytosis activity of macrophage-like J774.1 cells and mouse peritoneal macrophages. In addition, OSA-PG increased the production of IL-6 and TNF-α by enhancing their gene expression. Immunoblot analysis displayed that OSA-PG tended to activate both nuclear factor-κB and mitogen-activated protein kinase cascades. Treatment of OSA-PG with polymyxin B revealed that cytokine production induced by OSA-PG was not caused by endotoxin contamination. Our findings also indicated that OSA-PG activates macrophages through not only Toll-like receptor (TLR) 4, but another receptor. Overall findings suggested that OSA-PG has a potential as an immunomodulatory food factor by stimulating macrophages.